Are rare hernias rarer: a ten-year observational study - Pande, Tanmay; Yadav, Arpan; Varghese, B. K.; Gupta, Anurakshat (International Surgery Journal, 2019)
Background: Hernia is one of the most common ailments encountered in general surgery practice. The inguinal hernia constitutes majority of cases. The available literature describes umbilical, femoral, lumbar, perineal and many others rarer varieties. Our preliminary observations indicated a changing scenario. With a view to ascertain it, investigations were made to find out the incidence of hernia with frequency data of different types and demographic details of patients during last decade at tertiary care teaching hospital in Pune and then comparing it with the existing literature. Methods: Ten years data from October 2008 to October 2018 of all the adult population suffering from hernia reporting to this center was collected from the archives of hospital records maintained in OPD, wards and the department. Results: Inguinal hernia was the most common constituting 76.9% of the total cases. The right side was more affected than the left side with 51.0% cases being on right side. This was followed by umbilical hernia, 12.26% of the total cases. Males were more affected than the females except in incisional hernia. Only two cases of spigelian hernia had undergone repair over last one decade. There were no cases of femoral hernia, lumbar hernia and perineal hernia encountered during the last ten years in this center. Conclusions: The relative frequency of the incidence of different types of hernia was inguinal, umbilical, epigastric; incisional which have been in descending order. In the last decade at this centre which is in contrast with hernia incidence ﬁgures quoted in common reference books and the available literature.